Synthesis and Structure–Activity Relationship Correlations of Gnidimacrin Derivatives as Potent HIV‑1 Inhibitors and HIV Latency Reversing Agents - Liu, Qingbo; Cheng, Yung-Yi; Li, Wei; Huang, Li; Asada, Yoshihisa; Hsieh, Min-Tsang; Morris-Natschke, Susan L; Chen, Chin-Ho; Koike, Kazuo; Lee, Kuo-Hsiung (Journal of medicinal chemistry, 2019)
Currently, due to the HIV latency mechanism, the search continues for effective drugs to combat this issue and provide a cure for AIDS. Gnidimacrin activates latent HIV-1 replication and inhibits HIV-1 infection at picomolar concentrations. This natural diterpene was able to markedly reduce the latent HIV-1 DNA level and the frequency of latently infected cells. Therefore, gnidimacrin is an excellent lead compound, and its anti-HIV potential merits further investigation. Twenty-nine modified gnidimacrin derivatives were synthesized and evaluated in assays for HIV replication and latency activation to establish which molecular structures must be maintained and which can tolerate changes that may be needed for better pharmacological properties. The results indicated that hydroxyl substituents at C-5 and C-20 are essential, while derivatives modified at 3-OH with aromatic esters retain anti-HIV replication and latent activation activities. The half-lives of the potent GM derivatives are over 20 h, which implies that they are stable in the plasm even though they contain ester linkages. The established structure–activity relationship should be useful in the development of gnidimacrin or structurally related compounds as clinical trial candidates.